Association between isolated external ear malformation and renal anomalies - Ismail, Izyan (2016)
Introduction. Congenital anomalies of renal and urinary tract and external ear malformation are both rare entity. There are multiple studies that concluded higher incidences of congenital renal anomalies in those with external ear malformation. Thus, this study was intended to determine the significance of the association between isolated external ear malformation and congenital renal anomalies. Objective. To determine the association between isolated external ear malformation and congenital renal anomalies. Methodology. Retrospectively, 125 subjects (study group) with sonography detected congenital anomalies of kidney and urinary tract (CAKUT) and 125 subjects with normal ultrasound kidney, ureter and bladder (KUB) (control group) were recruited from two centres; Hospital Tengku Ampuan Afzan (HTAA) and Hospital Universiti Sains Malaysia (HUSM). Images were reviewed using Picture Archiving and Communication systems (PACS). Presence of isolated external ear malformation i.e preauricular appendages, sinus and pinna abnormality were identified through either the case notes or the Radiology Information System (RIS). Results. Urinary tract abnormalities with isolated external ear malformation were detected in 6 subjects. Five subjects with preauricular sinus have renal agenesis (2 subjects), vesicoureteric reflux (VUR) (1 subjects), renal duplex (1 subject) and ureterocoele (1 subject) respectively; and one subject with pinna abnormality had VUR. Pearson chi-square (X2) test analysis proved non-significant association between these two groups (p>0.05). Conclusions. There is a no significant association between isolated external ear malformation and congenital renal anomalies; hence routine ultrasound KUB is not mandataory.